Structural Characterization of Monoclonal Antibodies and Epitope Mapping by FFAP Footprinting - Fojtík, Lukáš; Kalaninová, Zuzana; Fiala, Jan; Halada, Petr; Chmelík, Josef; Man, Petr; Kukačka, Zdeněk; Novák, Petr (Analytical chemistry, 2024)
Covalent labeling in combination with mass spectrometry is a powerful approach used in structural biology to study protein structures, interactions, and dynamics. Recently, the toolbox of covalent labeling techniques has been expanded with fast fluoroalkylation of proteins (FFAP). FFAP is a novel radical labeling method that utilizes fluoroalkyl radicals generated from hypervalent Togni reagents for targeting aromatic residues. This report further demonstrates the benefits of FFAP as a new method for structural characterization of therapeutic antibodies and interaction interfaces of antigen-antibody complexes. The results obtained from human trastuzumab and its complex with human epidermal growth factor receptor 2 (HER2) correlate well with previously published structural data and demonstrate the potential of FFAP in structural biology.
Keywords: imunokomplex; halogenace; footprinting proteinů; Receptor, ErbB-2; monoklonální protilátky; Trastuzumab; Epitope Mapping; receptor erbB-2; lidé; Antibodies, Monoclonal; Protein Footprinting; alkylace; Humans; Halogenation; Antigen-Antibody Complex; mapování epitopu; Alkylation; trastuzumab